Home‐Based Exercise in Patients Awaiting Liver Transplantation: A Feasibility Study. Issue 7 (6th June 2019) - Williams, Felicity Rhian; Vallance, Alice; Faulkner, Thomas; Towey, Jennifer; Durman, Simon; Kyte, Derek; Elsharkawy, Ahmed Mohamed; Perera, Thamara; Holt, Andrew; Ferguson, James; Lord, Janet M.; Armstrong, Matthew James
Abstract : Frailty is associated with increased mortality both before and after liver transplantation (LT). There are no standardized exercise programs, in particular home‐based exercise programs (HBEPs), for patients awaiting LT. The aim was to investigate the feasibility of such a program in patients awaiting LT. Patients were randomly selected from the Birmingham LT waiting list and provided with a 12‐week HBEP, including average daily step (ADS) targets and twice‐weekly resistance exercises. Feasibility was based on patient eligibility (≥66% of waiting list), target recruitment (≥90% of n = 20), safety (no related serious adverse events), and adherence (≥66% adherence to 6‐week HBEP). Measures of aerobic (incremental shuttle walk test [ISWT], ADS), functional capacity (short physical performance battery test [SPPBT]), and health‐related quality of life (EuroQol 5‐Dimension 5‐Level (EQ‐5D‐5L) and hospital anxiety and depression score [HADS]) were taken at baseline and at 6 and 12 weeks. 18 patients (50% male; median age, 55 years) were recruited. All domains of the study feasibility criteria were met. ISWT improved after 6 weeks (50 m; P ≤ 0.01) and 12 weeks (210 m; P ≤ 0.01), despite withdrawal of the telephone health calls. Similarly, improvements were seen in ADS (2700/day; P ≤ 0.01) and the SPPBT (2.5; P = 0.02) after 12 weeks. There was no difference in HADS (median difference [MD] –3; P = 0.69), but EQ‐5D‐5L after 12 weeks (17.5%; P = 0.04). In conclusion, a 12‐week HBEP, incorporating both easy‐to‐apply resistance and aerobic exercises, is safe and feasible in patients awaiting LT. Measures of aerobic and functional capacity demonstrate trends toward improvement that warrant further investigation in a randomized controlled trial.